Genetic diversity of cassava (Manihot esculenta Crantz) landraces and cultivars from southern, eastern and central Africa - Kawuki, Robert S.; Herselman, L.; Labuschagne, Maryke T.; Nzuki, I.; Ralimanana, I.; Bidiaka, M.; Kanyange, M.C.; Gashaka, G.; Masumba, E.; Mkamilo, G.S.; Gethi, J.; Wanjala, Bramwel W.; et al. (Cambridge University Press, 2013)
Studies to quantify genetic variation in cassava germplasm, available within the national breeding programmes in Africa, have been limited. Here, we report on the nature and extent of genetic variation that exists within 1401 cassava varieties from seven countries: Tanzania (270 genotypes); Uganda (268); Kenya (234); Rwanda (184); Democratic Republic of Congo (DRC; 177); Madagascar (186); Mozambique (82). The vast majority of these genotypes do not exist within a formal germplasm conservation initiative and were derived from farmers' fields and National Agricultural Research Systems breeding programmes. Genotypes were assayed using 26 simple sequence repeat markers. Moderate genetic variation was observed with evidence of a genetic bottleneck in the region. Some differentiation was observed among countries in both cultivars and landraces. Euclidean distance revealed the pivotal position of Tanzanian landraces in the region, and STRUCTURE analysis revealed subtle and fairly complex relationships among cultivars and among landraces and cultivars analysed together. This is likely to reflect original germplasm introductions, gene flow including farmer exchanges, disease pandemics, past breeding programmes and the introduction of cultivars from the International Institute of Tropical Agriculture – Nigeria. Information generated from this study will be useful to justify and guide a regional cassava genetic resource conservation strategy, to identify gaps in cassava diversity in the region and to guide breeding strategies.